Cross-cultural approaches to adoption - Bowie, Fiona (European Association of Social Anthropologists (Series), 2004)
The articles in this volume look at adoption practices from around the world, including examples of societies in which children are routinely separated from their biological parents. The text illustrates the range & flexibility of child-rearing practicesthat approximate to the Western term 'adoption'.